Assemblage structure of ichthyoplankton in the NE Atlantic in spring under contrasting hydrographic conditions - Rodriguez, J. M. (Sci Rep, 2019)
The ichthyoplankton assemblage in the Atlantic region off the NW Iberian peninsula (AR) and in the southern Bay of Biscay (SBB) and the response of the larval fish species distribution to the relatively rapidly changing hydrographic conditions in spring 2010 were studied using two ichthyoplankton cruises. The SBB showed a more abundant and diverse ichthyoplankton assemblage than the AR, although the larval fish assemblage (LFA) was structured into on-shelf and off-shelf assemblages in both regions. Inter-sampling variability related to downwelling/upwelling regimes was observed in the cross-shelf assemblage distribution in the SBB but not in the AR. This suggests that LFA distributions in the area of this study are good indicators of downwelling and weak coastal upwelling regimes but not of relatively strong coastal upwelling or upwelling filaments. Although depth was identified by multivariate analyses as being the most important variable explaining larval fish species distributions, a shelf-breakfront in the SBB and the surface offshore (onshore) flows associated with coastal downwelling (upwelling) in the AR seems to have been key in defining and maintaining assemblage boundaries. Results of this study should also encourage marine research institutions to use routine ichthyoplankton sampling to monitor fish communities and their responses to global warming.